Akteursnetzwerke und Regionalentwicklung im Schatten von Gorleben: Der Landkreis Lüchow-Dannenberg - Masurek, Lars; Hachmöller, Gerd (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
In the course of the EU research project DORA (Dynamics of Rural Areas), the Institute of Farm Economics and Rural Studies at the Federal Research Institute for Agriculture (FAL) analyses factors which influenced the economic performance of rural areas in the last two decades. Next to bottlenecks in terms of infrastructure, human capital and industrial structure, the county Luechow-Dannenberg suffers from a marked social and political segmentation of the local community, which is rooted in the ongoing dispute about the nuclear waste facilities in the village of Gorleben. This paper analyses social capital in the region and network structures between the decision makers. The study reveals that the local actor network is clearly segmented into opposing groups and it proves difficult for the regional community to reach consensus about measures for regional development. As a result regional decision making processes and economic development are decisively obstructed.
Keywords: Article